2023
DOI: 10.3390/physiologia3020022
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Lipid Mediators in the Mechanisms of Exercise-Induced Muscle Damage

Athanasios G. Gakis,
Tzortzis Nomikos,
Anastassios Philippou
et al.

Abstract: Lipid mediators are a class of signaling molecules that play important roles in various physiological processes, including inflammation, blood pressure regulation, and energy metabolism. Exercise has been shown to affect the production and metabolism of several types of lipid mediators, including prostaglandins, leukotrienes, sphingolipids, platelet-activating factors and endocannabinoids. Eicosanoids, which include prostaglandins and leukotrienes, are involved in the regulation of inflammation and immune func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…These glycemic responses might also be a result of possible muscle damage which the resistance exercise could have caused the sedentary patients of our study. Indeed, previous studies have shown a reduction in insulin sensitivity because of a strong inflammatory response and a decrease in glucose transporter GLUT4 following exercise-induced muscle damage [36], which may result in a "protective", temporary state of insulin resistance to the high mechanical and metabolic stress and the consequent muscle damage [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…These glycemic responses might also be a result of possible muscle damage which the resistance exercise could have caused the sedentary patients of our study. Indeed, previous studies have shown a reduction in insulin sensitivity because of a strong inflammatory response and a decrease in glucose transporter GLUT4 following exercise-induced muscle damage [36], which may result in a "protective", temporary state of insulin resistance to the high mechanical and metabolic stress and the consequent muscle damage [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%